A critical review of postfeminist sensibility. Issue 12 (12th December 2017) - Riley, Sarah; Evans, Adrienne; Elliott, Sinikka; Rice, Carla; Marecek, Jeanne
Abstract: This paper critically reviews how feminist academic psychologists, social scientists, and media scholars have developed Rosalind Gill's generative construct "postfeminist sensibility." We describe the key themes of postfeminist sensibility, a noncoherent set of ideas about femininity, embodiment, and empowerment circulating across a range of media. Ideas that inform women's sense of self, making postfeminist sensibility an important object for psychological study. We then consider research that drew on postfeminist sensibility, focusing on new sexual subjectivities, which developed analysis of agency, empowerment, and the possibilities and limitations in taking up new subjectivities associated with postfeminism, as well as who could take up these subjectivities. We show how such work identified complexities and contradictions in postfeminist sensibility and offer suggestions for how this work might be further developed, particularly by intersectionality‐informed research. In the final section, we address contemporary debates surrounding postfeminism. We consider challenges and counterarguments to postfeminist sensibility as a useful term for describing contemporary patterns of sense‐making on gender, making the case for continuing research on postfeminist sensibility in the areas of digital cultures, a transformative imperative that includes the mind as well as the body, transnational postfeminism, and new forms of feminist activism. We conclude that such work would benefit from considering the ways that different technologies mediate the ideas and practices associated with postfeminist sensibility.